Analisis Pengakuan, Pengukuran, Pengungkapan, dan Penyajian Aset Biologis Berdasarkan Standar Akuntansi Keuangan Pada PT.Perkebunan Nusantara IX (Persero) - Sari, Ana Yuwanita, Dr. Triyono, SE, M.Si (2015)
The study entitled analyzes the recognition, measurement, disclosure and presentation of biological asset based on financial accounting standar in PT. Perkebunan Nusantara IX (Persero). The aims to determine the actual practices of biological asset accounting treatment in the field and then try to sprace up the accounting treatment based on financial accounting standard (SAK). This study compares the treatment of biological asset with the treatment of biological standard based on financial accounting in the company. The study carried out by the method of qualitative analysis through case study on one of the enterprise owned by the state (BUMN). Farm sector namely PT. Perkebunan Nusantara IX (Persero). The data used are secondary which are taken from the financial report on the year 2013. The data processed by the method of comparative analysis to determine differences in the accounting treatment of biological asset. The result of the study showed that there was no significant difference between the recognition, measurent, disclosure, and presentation of biological asset between companies and SAK.